2018
DOI: 10.1177/2472555217750871
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of In Vitro Selection Assays of DNA-Encoded Peptidomimetic Ligands to CBX7 and CBX8

Abstract: The identification of protein ligands from a DNA-encoded library is commonly conducted by an affinity selection assay. These assays are often not validated for robustness, raising questions about selections that fail to identify ligands and the utility of enrichment values for ranking ligand potencies. Here, we report a method for optimizing and utilizing affinity selection assays to identify potent and selective peptidic ligands to the highly related chromodomains of CBX proteins. To optimize affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…Our observations are largely in keeping with the results of Krusemark and co‐workers, who studied the efficiency of affinity capture selections by using DNA‐encoded peptides, which were capable of binding to CBX . The authors found that lower enrichments and recoveries of ligands were obtained for lower ligand affinity to both CBX7 and CBX8 ChDs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations are largely in keeping with the results of Krusemark and co‐workers, who studied the efficiency of affinity capture selections by using DNA‐encoded peptides, which were capable of binding to CBX . The authors found that lower enrichments and recoveries of ligands were obtained for lower ligand affinity to both CBX7 and CBX8 ChDs .…”
Section: Discussionmentioning
confidence: 99%
“…Our observations are largely in keeping with the results of Krusemark and co‐workers, who studied the efficiency of affinity capture selections by using DNA‐encoded peptides, which were capable of binding to CBX . The authors found that lower enrichments and recoveries of ligands were obtained for lower ligand affinity to both CBX7 and CBX8 ChDs . If the findings of both studies are confirmed for other proteins, there might be a need to develop more efficient selection methods, particularly for targets for which only hits with micromolar potency can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting chromatin reader proteins using DELs requires an approach to diminish non-specific DNA interactions interfering during the selections, as many of these proteins are highly basic and in fact coordinate with DNA [68][69][70]. Studies from the Krusemark lab have shown the utility of DELs for chromodomain containing proteins by producing a DEL of peptidomimetics [71,72]. To address the feasibility of DELs for chromatin readers in our hands and to establish general selection and sequencing protocols, we explored a model system using the chromodomain-containing Kme reader protein CBX7, which is part of the multi-subunit protein complex Polycomb Repressive Complex 1 [56].…”
Section: Production Of Barcoded Control Compounds To Inform Del Selecmentioning
confidence: 99%
“…This may also contribute to the observation that a larger number of DEL literature reports describe the identification of enzyme inhibitors binding to well defined pockets [8]. Nonetheless, the number of examples successfully identifying binders to challenging targets like PPIs [63,65,66,88,89] and MoAs such as agonists, positive allosteric modulators and antagonists for G-protein coupled receptors (GPCRs) [67,68,90,91,92] grows at an increasing rate. Key contributors to the recent success against GPCRs were advances in production of membrane proteins [93] and stabilization of specific conformations [94,95].…”
Section: Applications Of Encoded Library Platforms In Drug Discoverymentioning
confidence: 99%